EKOSISTEM TERUMBU KARANG SEBAGAI OBJEK WISATA BAHARI DI KAWASAN PEMUTERAN, BUUELENG: POTENSI DAN ANCAMANNYA - Witari, Made (Pusat Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Nusa Dua Bali, 2007)
This article aims at analysing the potentials of and threats to the coral reefsin Pemuteran, Buleleng, Bali, as a tourist resorts. Coral reefs have the potentialsto atrract tourists visit and therefore preserving them provides somebenefits economically and ecological). However there are some threats to thesustuinability of the coral reefs ecosystem. In order to maximize the benefitsand preserve the ecosystem, tourism businessmen and NGOs involve the localcommunity in managing and preserving the coral reefs.